Rare primary patellar resurfacing does not lead to more secondary patellar resurfacing: analysis of 70,014 primary total knee arthroplasties in the Dutch Arthroplasty Register (LROI) - Robben, Bart J; de Vries, Astrid J; Spekenbrink-Spooren, Anneke; Nelissen, Rob G H H; Brouwer, Reinoud W (Acta Orthopaedica, 2022)
Background and purpose: Current literature provides no conclusive evidence in support of a patellar resurfacing vs. non-resurfacing regime. Therefore, we compared the incidence of secondary patellar resurfacing among hospitals using 3 different primary patellar resurfacing regimes in the Netherlands. Secondarily we identified patient and surgical characteristics associated with primary patellar resurfacing and secondary patella resurfacing following non-resurfaced primary total knee arthroplasty (TKA). Patients and methods: We used data from 2014–2016 of the Dutch Arthroplasty Register. Hospitals were divided into rare (0–10%), selective (>10% to 90%), and usually primary patellar resurfacing (>90%) regimes. We performed a logistic regression analysis for associated factors of primary patellar resurfacing in the selective resurfacing subgroup and for secondary patellar resurfacing in the rare resurfacing subgroup. Results: The rate of primary resurfacing was 5.2% for the rare and 36% for the selective patellar resurfacing regimes, with similar secondary patellar resurfacing (1.1% vs. 0.9%). Predictors for primary patellar resurfacing were being female (OR 1.3) and younger (50–59 years, OR 1.4). The PS prosthesis design had a higher OR (4.1) than the CR design. Younger age (50–59 years, OR 1.5) and PS prosthesis (OR 2.7) were significant predictors of secondary patellar resurfacing. Particular surgical systems have a higher rate of primary and secondary patellar resurfacing. Interpretation: Low rates of secondary patellar resurfacing in hospitals with a rare resurfacing regime indicate that this regime does not lead to more secondary patellar resurfacing then selective resurfacing. In the Dutch orthopedic community primary and secondary patellar resurfacing is associated with using a posterior stabilizing design, being younger, and using particular TKA systems.